Economic analysis of the inclusion of thermoelectric ash in asphalt mixtures (Research, Society and Development, 2021)
The replacement of conventional materials used in hot asphalt mixtures with others of good technique and lower cost and environmental impact has motivated research in this area of knowledge in recent decades. The researches should be expanded in the scope of engineering, given that it contributes considerably to the transformation of spaces and raw material. In this context, thermoelectric ashes, which are residues from the production of electric energy, appear as an alternative to replace the stone powder input which contributes negatively to the environment considering that it comes from the blasting of rocks. This work aims to compare the cost of producing traditional asphalt concrete (reference) to asphalt compositions containing 5,15% of alternative material characterized by stone dust. There was a saving of R$ 0.21 per ton of AC machining, consisting of thermoelectric ash as a partial substitute (5.15%) for stone powder, which represents significant savings in a practical context.